2000
DOI: 10.1177/107155760000700411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Oral Contraceptive Combination With or Without Androgen on Mammary Tissues: A Study in Rats

Abstract: Our results suggest that a medication containing an estrogen-progestin-androgen combination has antiproliferative effects in mammary glands of experimental animals that could prove to have breast-protective potential in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Studies on rhesus monkeys demonstrate the inhibiting influence of androgens on mammary epithelial proliferation by reducing E2-induced proliferation [48,49]. The same results have been shown in rodent mammary gland [50]. Observations indicate similar effects of androgens in humans.…”
Section: Inhibition Of Proliferation In the Normal Mammary Glandsupporting
confidence: 71%
“…Studies on rhesus monkeys demonstrate the inhibiting influence of androgens on mammary epithelial proliferation by reducing E2-induced proliferation [48,49]. The same results have been shown in rodent mammary gland [50]. Observations indicate similar effects of androgens in humans.…”
Section: Inhibition Of Proliferation In the Normal Mammary Glandsupporting
confidence: 71%
“…Short-term, low doses of several forms of androgens have been shown to inhibit the estrogen-induced proliferation of the mammary epithelial cells in adult female rats, mice, and monkeys [177,178]. Similar inhibitory effects are also observed in human and rat mammary glands in vitro [179,180].…”
Section: Ar Roles In Breast Developmentmentioning
confidence: 86%
“…Supporting this view, a recent study found that a low-dose oral contraceptive induced robust mammary epithelial proliferation in rats, but that addition of methyltestosterone to the therapy significantly suppressed the proliferation. 23 It is important to keep in mind, however, that species-specific differences in steroid production and metabolism may influence net steroid effect upon mammary and other tissues.…”
Section: Dimitrakakis Et Almentioning
confidence: 99%